Experimental design of reversed-phase high performance liquid chromatographic conditions for simultaneous determination of ibuprofen, pseudoephedrine hydrochloride, chlorpheniramine maleate, and nipagen - Asci, B.; Donmez, O. A.; Bozdogan, A.; Sungur, S. (MAIK NAUKA/INTERPERIODICA/SPRINGER, 2010)
2(5-1) fractional factorial design was applied to optimize the chromatographic conditions of the RP-HPLC determination of ibuprofen, pseudoephedrine hydrochloride, chlorpheniramine maleate, and nipagen in syrup preparation. All the factors that affect the determination of components and their interactions were investigated. pH, flow rate and solvent ratios for three steps of gradient profile were regarded as factors to be investigated in two levels. The resolution was chosen as analytical response. The limit of quantitations (10 s/m) were found as 0.9, 1.0, 0.4, and 0.12 mu g/mL for ibuprofen, pseudoephedrine hydrochloride, chlorpheniramine maleate, and nipagen, respectively.
Keywords: HUMAN PLASMA; SPECTROPHOTOMETRIC METHODS; PHARMACEUTICAL-PREPARATION; MASS-SPECTROMETRY; OPTIMIZATION; HPLC; INGREDIENTS; SEPARATION; MIXTURES; SAMPLES; Chemistry